Distinct pseudokinase domain conformations underlie divergent activation mechanisms among vertebrate MLKL orthologues - Katherine A. Davies (Nature Portfolio, 2020)
The necroptotic cell death pathway involves signaling through pseudokinases. Here the authors define the structural determinants of species specificity in necroptosis signaling mediated by the essential necroptotic effector pseudokinase, Mixed Lineage Kinase Domain-Like (MLKL).